Fair Play in Physical Education: Effects of Sex, Age and Intrinsic Motivation - Papageorgiou Μαρία; Hassandra Μαρία; Hatzigeorgiadis Αντώνης (Inquiries in Physical Education and Sport, 2008)
The purpose of the present study was to examine fair play behaviors in a physical education context in relation to demographic characteristics and motivational variables. Participants were 472 primary (n = 248) and secondary (n = 148) school students (M= 12.62 ± 1.70 yrs). Students completed in their class environment in the absence of their physical education teacher a form containing the Intrinsic Motivation Inventory (IMI) and the Fair Play in Physical Education Questionnaire (FPPEQ). Correlation analysis revealed that overall the intrinsic motivation dimensions were positively related to pro-social behavior and negatively related to anti-social behavior. Twoway (2 x 2) MANOVA was calculated to test for differences in fair play between sex and education level (primary – secondary). The results revealed boys scored higher than girls on gamesmanship and cheating (p<.05) and lower than girls on respect for teammates (p<.05). Furthermore, it was revealed that secondary school students scored higher on the anti-social behaviors (p<.01) and lower on the pro-social behaviors (p<.05) than primary school students. Finally, it was revealed that secondary school boys scored lower on respect for teammates that secondary school girls and primary school students (both primary and secondary).